2020
DOI: 10.1002/mus.27001
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐sectional area reference values of the median nerve at the palm using ultrasound

Abstract: BackgroundThe most common neuromuscular ultrasound abnormality in carpal tunnel syndrome is enlargement of the median nerve near the distal wrist crease, but sometimes the median nerve enlarges in the palm, just distal to the transverse carpal ligament. This study was conducted to devise a protocol for measuring the median nerve in the palm and to generate reference values for nerve cross‐sectional area at this site.MethodsA systematic protocol was developed, 30 healthy individuals underwent ultrasound of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…We suggest that the therapeutic effect of direct TENS in the treatment of diabetic distal polyneuropathy is not significantly different from the therapeutic effect in the treatment of GBS. This effect is achieved by accelerating functional recovery, nerve fiber remyelination [ 25 ] and axonal regeneration [ 24 ] and increasing the regenerative capacity of peripheral nerves [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…We suggest that the therapeutic effect of direct TENS in the treatment of diabetic distal polyneuropathy is not significantly different from the therapeutic effect in the treatment of GBS. This effect is achieved by accelerating functional recovery, nerve fiber remyelination [ 25 ] and axonal regeneration [ 24 ] and increasing the regenerative capacity of peripheral nerves [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most studies of ultrasound and MRI have found enlargement of the nerve proximal to the carpal tunnel to be a reliable parameter to predict CTS. 19,[22][23][24] Ng et al using MRI found that the absolute value of median nerve CSA > 0.15cm 2 either proximal or distal to the carpal tunnel was diagnostic for CTS. 18 It is possible that this parameter was a better indicator for elevated pressure within the carpal tunnel than chart diagnosis of CTS.…”
Section: Discussionmentioning
confidence: 99%